Considerations and Changes in the Evaluation, Management, and Outcomes in the Management of Diverticular Disease: The Diagnosis, Pathology, and Treatment of Diverticular Colitis - Kucejko, Robert J.; Poggio, Juan L. (Clinics in Colon and Rectal Surgery, 2018)
Diverticular colitis, also known as segmental colitis associated with diverticulosis, is a colonic inflammatory disorder on the spectrum of inflammatory bowel disease (IBD). The disease consists of macroscopic and microscopic inflammation affecting inter-diverticular mucosa, sparing peri-diverticular mucosa, with inflammation confined to the descending and sigmoid colon. The disease likely arises from the altered immune response of an individual, genetically susceptible to the IBD spectrum of diseases. Patients with segmental colitis associated with diverticulosis (SCAD) are typically older, and likely represent a subgroup of IBD—susceptible patients who lacked an environmental trigger until that point in their life. Most patients remain in remission with initial treatments of mesalamine or topical steroids, and maintenance mesalamine afterwards. Only the most severe form of the disease necessitates immunomodulatory therapy and the consideration of surgery.
Keywords: diverticular; segmental; sigmoid; diverticulosis; colitis